Assessment of hyperactivity-impulsivity and attention deficit in adolescents by self-report and its association with psychopathology and academic performance - Saura-Garre, Pedro; Vicente-Escudero, Jose L.; Checa, Silvia; Castro, Maravillas; Fernández, Visitación; Alcántara, Mavi; Martínez, Antonia; López-Soler, Concepción (Frontiers in Psychology, 2022)
The scientific literature highlights the risk of the appearance of internalizing and externalizing symptoms, together with difficulties in the academic area, linked to diagnosis of Attention Deficit Hyperactivity Disorder (ADHD). This is normally assessed by teachers and primary caregivers, disregarding the self-perception of the adolescents themselves, which limits detection of this disorder at an evolutionary stage. Our aim was to analyze the psychometric properties of a self-report for ADHD in adolescence and its relationship with psychopathology and academic performance. This study assessed an incidental sample of 267 students from secondary schools in the Region of Murcia, Spain, using the EDAH questionnaire adapted for self-report, in order to analyze its psychometric properties in assessing ADHD. The YouthSelf-Report (YSR) and the BriefSelf-Control Scale (BSCS) were also used to determine their association with psychopathological, self-control and academic performance variables. An ADHD prevalence of between 3.7% and 13.1% was observed depending on the established cut-off point. The adapted EDAH showed adequate reliability indices (α = .818) and explained a high variance percentage (50.655%). Adolescents with anxiety/depression difficulties, dissocial behavior, aggressiveness and poor performance in mathematics showed a higheramount of ADHD symptoms. Moreover, self-control, dissocial behavior, age and performance in Social Sciences acted as predictors of the disorder. The good psychometric properties of this questionnaire and its adequate correspondence with other variables of interest suggest it is an appropriate self-report instrument to assess ADHD in adolescence.